Respiro Luego Actúo Un Encuentro Transformador En La Vida De Un Maestro De Teatro (2024)
This thesis focuses on the reconstruction of the artistic-pedagogical life story of the teacher in training for the Bachelor of Performing Arts, Fabián Ricardo Copete Torres, and his transformative experience with the Sudarshan Kriya (SKY) breathing technique. This project, registered in the Teachers' Thought Line and within the framework of the Performing Arts Didactic Research Group, explores how breathing, relaxation and meditation techniques, integrated into theatrical pedagogy, can contribute to the emotional well-being and integral development of performing arts students.